A Technique: Examining the Evidence - Serkan AKKOYUNLU; Mehmet Hakan TÜRKÇAPAR (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Introduction: Cognitive therapy is based on the realistic epistemology which exerts that there is an objective reality beyond human experience. Cognitive models of psychopathology stipulate that the processing of external event or internal stimuli is biased and therefore systematically distorts the individual’s construction of his or her experiences, leading to a variety of cognitive errors. These distorted cognitions predispose or perpetuates mental disorders. If this bias that is also manifested in the automatic thoughts during specific instances can be attenuated by weakening the belief in these thoughts, it may lead into change in the accompanying emotion and dysfunctional behaviour. Objective: The aim of this review is to describe the basic technique of cognitive therapy namely “examining the evidence” and also present the clinical application of this technique. In order to perform this technique, first situation must be detailed. Then assessed emotion is graded according to its severity. After that, key automatic thought must be identified and phrased accordingly. After grading belief in the thought, evidence for and against the thought can be generated using appropriate questioning. In the end by using this evidence, the belief in the automatic thought and the emotion must be reviewed. Examining the evidence can also be used as a homework assignment to be done between sessions. In this text, steps of examining the evidence, which questions to be asked, and the points that must be attendant is reviewed and a sample interview is included. Conclusion: By its empirical nature “examining the evidence” is the most valuable technique of cognitive therapy and when it is applied properly long lasting change can occur in clients. [JCBPR 2012; 1(3.000): 184- 190]